Colorectal Lesions among Sudanese Patient Attending for Endoscopy-multi Center Study - Mohammed Mukhtar, Ashwag; Hussein, Tarig Mohamad; Abbas, Amin; Abdelaziz, Mutaz SalahEldin; Alhaboob, Nasir; Gady, Elsagad Eltayeb; ElHassan, Lamya (Asian Pacific Journal of Cancer Care, 2021)
Background: Colorectal cancer is one of the most significant causes of cancer death. With records of high incidence and late detection of the disease in Sudan, and it was found to affect younger age groups. Methods: This study aimed to explore the incidence of colorectal lesions in the main endoscopic centers in Khartoum state- Sudan. It was a cross-sectional prospective study; data were collected from patients attending the main endoscopic centers in Sudan- Khartoum state during February 2013 to June 2014 including Khartoum teaching hospital, Neelain medical diagnostic center and Ibn sina hospital. Results: One hundred and six participants were diagnosed endoscopically with colorectal lesions, 44 (41.5%) showed inflammatory mucosa, 40 (37.7 %) showed tumor and 22 (20.7%) had polyps. In the whole group of patients the mean age was 45.7 years, 34.2% of tumor patients were less than 50 years old, 46.8% of the lesions were in the rectum, the highest frequency of tumor patients group were from western tribes, and the lesions were located commonly in the rectum. Conclusion: We concluded that the rectum is the most common site of cancer within the Sudanese population than other parts of the colon with apparently high incidence within young ages.